(untitled) (Fisioterapia e Pesquisa, 2013)
The Angelman syndrome is characterized by neuromotor difficulties, such as ataxic gait and delayed acquisition of motor skills. However, there are few studies investigating the effect of interventions directed to this population. This study aimed to investigate the effect of a balance training in a child with Angelman syndrome. The participant was a nine-year-old girl. The training protocol was implemented during an eight-week period, twice a week, and consisted of activities involving static balance under various difficulty levels. After the training, the postural sway measured by biophotogrammetry changed from 38° to 13.78°. The scores in the Berg scale changed from 27 points to 37 points. In the Timed Up & Go test, the child's time to complete the task changed from 15 to 12 seconds. Taken together, the results suggest that the training led to improved static and dynamic balance, as well as functional mobility.